Anterior and Posterior Instrumentation for Treatment of Fracture by Vertebral Metastasis (International Journal of Medical and Surgical Sciences, 2017)
Tumoral fractures in spine are part of the etiology of pathologic fractures in this level, age of presentation and the observed clinical can give guidance on the type of tumor that affects the axial skeleton, it is important to identify, classification and therapeutic to follow, especially those who are affected neurological distal part. Considering this aspect propose clinical case below.